2012
DOI: 10.1007/s10194-012-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Migraine prevalence, alexithymia, and post-traumatic stress disorder among medical students in Turkey

Abstract: The aim of this study was to investigate the prevalence of migraine, alexithymia, and post-traumatic stress disorder among medical students at Cumhuriyet University of Sivas in Turkey. A total of 250 medical students participated in this study and answered the questionnaires. The study was conducted in three stages: the self-questionnaire, the neurological evaluation, and the psychiatric evaluation. In the first stage, the subjects completed a questionnaire to assess migraine symptoms and completed the three-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 46 publications
5
45
2
6
Order By: Relevance
“…It was found that the prevalence of migraine was comparable between medical and non‐medical students, which is contradictory to previous findings that more medical students suffer from migraine because they endure more psychological and physical stressors . However, this may be misleading if additional influential factors are not considered.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the prevalence of migraine was comparable between medical and non‐medical students, which is contradictory to previous findings that more medical students suffer from migraine because they endure more psychological and physical stressors . However, this may be misleading if additional influential factors are not considered.…”
Section: Discussionmentioning
confidence: 99%
“…In general population studies, 22‐26% of those with migraine fulfilled PTSD criteria, as compared to only 5% of those without headache and 14% of those with nonmigraine headache or no headache . Not surprisingly, in special populations with headache disorders (eg, pain clinic patients, veterans, and medical students) PTSD prevalence rates have been estimated at higher rates, approximately 22‐59% …”
Section: Introductionmentioning
confidence: 99%
“…In a sample of medical students in Turkey, migraine was associated with alexithymic personality traits and comorbid psychiatric disorders [4]. There is also evidence of a positive association between alexithymia, depression and anxiety in migraine patients.…”
Section: Introductionmentioning
confidence: 99%